The structure of p53 tumour suppressor protein reveals the basis for its functional plasticity - Okorokov, Andrei L (2006)
p53 major tumour suppressor protein has presented a challenge for structural biology for two decades. The intact and complete p53 molecule has eluded previous attempts to obtain its structure, largely due to the intrinsic flexibility of the protein. Using ATP-stabilised p53, we have employed cryoelectron microscopy and single particle analysis to solve the first three-dimensional structure of the full-length p53 tetramer (resolution 13.7 Å). The p53 molecule is a D2 tetramer, resembling a hollow skewed cube with node-like vertices of two sizes. Four larger nodes accommodate central core domains, as was demonstrated by fitting of its X-ray structure. The p53 monomers are connected via their juxtaposed N- and C-termini within smaller N/C nodes to form dimers. The dimers form tetramers through the contacts between core nodes and N/C nodes. This structure revolutionises existing concepts of p53's molecular organisation and resolves conflicting data relating to its biochemical properties. This architecture of p53 in toto suggests novel mechanisms for structural plasticity, which enables the protein to bind variably spaced DNA target sequences, essential for p53 transactivation and tumour suppressor functions.